Answers

2015-09-05T20:31:06+05:30
Log base 10 (log base 2 (log base 3 9) = x                                                         or, x = log base 10 (log base 2 (log base 3 9)                                                   or, x = log base 10 (log base 2 (log base 3 3^2)                                            or, x = log base 10 (log base 2 (2 log base 3 3)                                                  or, x = log base 10 (log base 2 2)                                                                     or, x = log base 10 1                                                                                           or, x = 0                       
 ∴ x = 0.Ans             
                          * You should say like this - log 9 to the base 3 or log  9  .                                                                                                                       3     
0